Anti-N-Methyl-d-Aspartate Receptor Encephalitis in a Patient with Alcoholism: A Rare Case Report - Li, Yangyang; Wang, Qiuling; Liu, Chuanxin; Wu, Yili (Frontiers in Psychiatry, 2017)
Anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis, the most common type of autoimmune encephalitis, is characterized by autoantibodies against NMDA receptor. Patients with anti-NMDAR encephalitis also present with various nonspecific symptoms, such as flu-like symptoms, neurological and psychiatric manifestations. Here we first reported a rare case of anti-NMDAR encephalitis in a 36-year-old male alcohol abuser. The patient presented with acute psychiatric symptoms with no abnormality of neuroimage exam and laboratory tests. Alcoholism was proposed the most likely diagnosis. However, stopping alcohol drinking and symptomatic treatment were not effective and 12 days later, the disease progressed with seizures and unconsciousness. Routine analysis of the cerebrospinal fluid (CSF) showed no abnormality. Importantly, anti-NMDA receptor antibodies were detected in his CSF, indicating the patient has anti-NMDA receptor encephalitis. Consistently, -immunoglobulin therapy dramatically improved symptoms, which further confirmed the diagnosis. As anti-NMDAR encephalitis has no unique clinical characteristic and its psychiatric manifestations may overlap with the alcoholism-associated psychiatric symptoms, the precaution should be taken to differentiate anti-NMDAR encephalitis with alcoholism in alcohol abusers.